Conceptualizing the nexus between social class and cognitive framework in Filipino women - Obligacion, Freddie R. (Philippine Journal of Psychology, 2004)
Using a casual modeling approach, this study delineated the cognitive consequences of women's socioeconomic status. Challenging common perception of the poor, low-socioeconomic-status respondent's showed a strong achievement orientation, self-efficacy, and high self-esteem. Low success expectations did not weaken motivation for self-improvement thanks to the compensating effects of a high regard forachievement, self-efficacy, and high self-esteem.